Dynamics of ionic liquids in bulk and in confinement by means of 1H NMR relaxometry – BMIM-OcSO4 in an SiO2 matrix as an example. Issue 33 (8th August 2016) - Kruk, Danuta; Wojciechowski, Milosz; Brym, Szczepan; Singh, Rajendra Kumar
Abstract : 1 H spin–lattice nuclear magnetic resonance relaxometry is applied to reveal the mechanisms of the ionic dynamics of BMIM-OcSO4 in bulk and in SiO2 nano-confinement. Abstract : 1 H nuclear magnetic resonance relaxometry is applied to reveal information on the translational and rotational dynamics of the ionic liquid: 1-butyl-3-methyl imidazoliumoctyl sulfate (BMIM-OcSO4 ) in bulk and in a confinement formed by a nanoporous SiO2 matrix. The experimental studies were performed in a very broad frequency range, from 8 kHz to 40 MHz (referring to the 1 H resonance frequency), in order to probe motional processes at very different time scales using a single experiment, and in the temperature range of 243–303 K. The relaxation results for BMIM-OcSO4 in bulk are interpreted in terms of three relaxation contributions: a term associated with the translational dynamics of the ions (it has been assumed that the translational dynamics of cations and anions can be described by one diffusion coefficient) and two terms associated with the rotational motion of the anion and the cation, respectively. The relationships between the obtained dynamic parameters (rotational correlation times and translational diffusion coefficients) are thoroughly discussed and used as a "reference" for the dynamics of BMIM-OcSO4 confined in an SiO2 matrix. Analysis of the corresponding relaxation data for the confined liquid shows that the confinement does not significantly affect the rotational dynamics, but it has a considerable impact on the translational motion. It is demonstrated that the relaxation term associated with the translational dynamics stems from two contributions: a contribution from a core (bulk-like) fraction of the liquid and from a fraction moving near the pore surface and therefore being for some time adsorbed on the pore walls. The translational diffusion coefficient for the last fraction is determined and several conclusions regarding the residence lifetime of the ions on the surface are drawn. Moreover, an additional motional process on the timescale of ns or shorter is revealed in the confinement.